THE ANALYSIS OF BANK SOUNDNESS USING RISK-BASED BANK RATING METHOD (RBBR) AT PT. BANKSULUTGO - Tuwo, Kevin Engelbert; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Bank Indonesia has issued a regulation concerning bank soundness assessment, which is Bank Indonesia Regulation (PBI) No. 13/1/PBI/2011. The regulation has stated that the bank is bound to conduct a soundness assessment by using risk approach (Risk-based Bank Rating). This research aims to assess the soundness of PT. Bank SulutGo (persero) Tbk from 2013 until 2017 using RBBR method. It is a descriptive quantitative research. The result shows that NPL ratio analysis is in very healthy condition while LRD ratio is in the less healthy condition in 2013, 2015 and 2016, and healthy enough condition in 2014 and 2017. GCG factor assessment shows that the bank is in a healthy condition. NIM and ROA ratios analysis show that the bank is in very healthy condition. CAR ratio analysis shows that the bank is in very healthy condition. This research has concluded that overall the bank is in a very healthy condition except in 2015, where the bank has been only in a healthy condition. It is recommended that PT. Bank SulutGo should keep balance of their credit towards deposit their received and put more effort on the management quality.Keywords: bank soundness, risk-based bank rating (rbbr) method.